1983
DOI: 10.1126/science.6301005
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Cholinergic Agents Induce Seizures and Brain Damage in Lithium-Treated Rats

Abstract: Administration of pilocarpine or physostigmine to rats treated with lithium chloride produced sustained limbic seizures, widespread brain damage, and increased concentrations of D-myo-inositol-1-phosphate (a metabolite of the phosphoinositides, lipids involved in membrane receptor function) in the brain. The syndrome was preventable with atropine. The physostigmine doses and concentrations of blood lithium that caused the syndrome are similar to those considered appropriate for psychiatric chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
147
1
7

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(167 citation statements)
references
References 32 publications
12
147
1
7
Order By: Relevance
“…Multiple rodent studies have shown that lithium treatment causes a sensitization to pilocarpine-induced seizures (Honchar et al, 1983;. Moreover, this enhanced sensitivity was shown to be reversed by replenishment of myo-inositol and not by its stereoisomer chiro-inositol that does not enter the PI cycle .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple rodent studies have shown that lithium treatment causes a sensitization to pilocarpine-induced seizures (Honchar et al, 1983;. Moreover, this enhanced sensitivity was shown to be reversed by replenishment of myo-inositol and not by its stereoisomer chiro-inositol that does not enter the PI cycle .…”
Section: Discussionmentioning
confidence: 99%
“…One in vivo demonstration of a lithium effect dependent on inositol is lithium pilocarpine-induced seizures. Rodents treated with lithium acutely or chronically are exquisitely sensitive to pilocarpine leading to a unique limbic seizure behavior (Honchar et al, 1983). This behavior is stereospecifically reversed by intracerebroventricular myo-inositol but not by its stereoisomer chiro-inositol, that does not enter the PI cycle .…”
Section: Introductionmentioning
confidence: 99%
“…One of the most robust behavioral effects of Li ϩ is that normally subconvulsant doses of muscarinic agonists will induce limbic seizures in rats pretreated with lithium (Honchar et al 1983). Induction of Li ϩ -pilocarpine seizures is concomitant with a reduction in cortical myo-inositol levels and an elevation of inositol monophosphate, which is about 10-fold greater than the effects elicited by either Li ϩ or pilocarpine alone (Sherman et al 1985a(Sherman et al , 1986.…”
Section: Inositol Reverses Li-pilocarpine Seizuresmentioning
confidence: 99%
“…Lithium (3mEq/kg) is injected in the rats 24 hours prior to pilocarpine injection. No seizures are produced if the interval of injecting lithium and pilocarpine is more than 48 hours (Honchar, Olney et al 1983). …”
Section: Pilocarpine Model Of Epilepsymentioning
confidence: 99%
“…Injecting lithium results in the requirement of much lower dose of pilocarpine (30mg/kg) for seizure generation (Honchar, Olney et al 1983;Curia, Longo et al 2008). The behavioral features of the rodents are characterized by "salivation, piloerection, tremor, chromodacryorrhea (bloody tears) and diarrhea" after five minutes of pilocarpine injection (Honchar, Olney et al 1983).…”
Section: Pilocarpine Model Of Epilepsymentioning
confidence: 99%